A perspectiva do negro: uma possibilidade de pensar a diáspora no Brasil - Conceição, Jessica Grava da [UNESP] (2015)
This study discusses the need and uses that there are about races references, in academia and in everyday life of Brazil. For such are worked some theories that link an innovative way to conceive the difference and its relation to the identity and representation. Afterwards it is made a brief analysis of social thought about blacks in Brazil, especially by theorists related to Social Sciences. Understanding how this concept can outline a spectrum of what being black in Brazil, will be analyzed some spaces where the idea of being black holds a different meaning appropriated by activists, religious and residents of black neighborhoods. Finally, the analysis focuses on some concepts that aim to contribute to the desired theoretical discussion, such as diaspora, différance and the concept of third space. It is intended in this way to break with the idea of a being black ontological that would remain, even if contrary to the logic of its constitution. However, pressing its historicity artificiality of creating a racial theory that divided the concept of human in a perverse hierarchy, legitimating of exploitation and abuse